Magnetic structure of an amorphous rare-earth transition-metal alloy - COEY, JOHN MICHAEL DAVID (American Physical Society, 1976)
161Dy Mossbauer spectra show that the dysprosium moments in amorphous DyCo3.4 are strongly coupled to the local crystal field axes. The magnetic structure is one in which the cobalt "sublattice" is strongly ferromagnetic, and the dysprosium moments are almost randomly distributed in directions between antiparallel and perpendicular to the cobalt.
PUBLISHED
Keywords: Physics